2013
DOI: 10.1016/j.tem.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The pancreatic β cell and type 1 diabetes: innocent bystander or active participant?

Abstract: Type 1 diabetes mellitus (T1DM) is a chronic disease resulting from destruction of insulin-producing pancreatic β cells. Genetic and environmental factors contribute to T1DM onset. Use of high-throughput DNA sequencing has allowed geneticists to perform genome-wide association studies (GWAS) to identify novel gene loci associated with T1DM. Interestingly, >50% of these genes encode products that are expressed in β cells. These studies, coupled with emerging molecular evidence that β cells are impaired by gain-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 99 publications
1
43
0
Order By: Relevance
“…These include several genes near DNA sequence variants (single nucleotide polymorphisms; SNPs) implicated by genome-wide association studies (GWAS) in genetic susceptibility to type 1 (T1D) and type 2 diabetes (T2D). These data support current views of the importance of islet (dys)regulation in T2D pathophysiology [19] and have rekindled interest in potential roles for islet transcriptional dysregulation in early or progressive pathophysiologic events leading to T1D [7], [20]. MicroRNA (miRNA) have also been profiled in human islets [21], [22]; a recent review describes their roles in post-transcriptional regulation and islet biology [23].…”
Section: The Expanding Islet Transcriptomesupporting
confidence: 61%
“…These include several genes near DNA sequence variants (single nucleotide polymorphisms; SNPs) implicated by genome-wide association studies (GWAS) in genetic susceptibility to type 1 (T1D) and type 2 diabetes (T2D). These data support current views of the importance of islet (dys)regulation in T2D pathophysiology [19] and have rekindled interest in potential roles for islet transcriptional dysregulation in early or progressive pathophysiologic events leading to T1D [7], [20]. MicroRNA (miRNA) have also been profiled in human islets [21], [22]; a recent review describes their roles in post-transcriptional regulation and islet biology [23].…”
Section: The Expanding Islet Transcriptomesupporting
confidence: 61%
“…ER stress in turn may serve as a trigger for autoimmunity (Tersey et al, 2012). The expression of ~60% of T1DM-associated genes in pancreatic islets further supports that the β-cell is more than an innocent bystander in its own demise, (Eizirik et al, 2012; Soleimanpour and Stoffers, 2013). …”
Section: Discussionmentioning
confidence: 70%
“…While T1DM is an autoimmune disease, many T1DM-associated genes are expressed in pancreatic β-cells, suggesting functions directly in β-cells that may contribute to disease pathogenesis (Eizirik et al, 2009; Soleimanpour and Stoffers, 2013). We previously found that Clec16a is expressed in pancreatic islets and that its expression is reduced in Pdx1 +/− islets (Sachdeva et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This cytokine cocktail induces expression of genes encoding for IL-12 and IFNγ in islets and beta cells [27]. With relevance to clinical diabetes, inflammation is a recognised component of the development of both type 1 and type 2 diabetes [1][2][3]. Concomitant with beta cell dysfunction and decreased islet survival, inflammatory cytokine stimulation increased 12-lipoxygenase gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Islet inflammation is a key contributor to loss of functional pancreatic beta cell mass in both type 1 and type 2 diabetes [1][2][3]. Studies have implicated inflammatory cytokines and immune cell infiltration leading to pathways, including oxidative and endoplasmic reticulum (ER) stress activation, that damage beta cell viability [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%